Influences on the reflection quality of journal writing: an exploratory study. Issue 5 (3rd September 2019) - Yu, Wai Ming; Chiu, Ming Ming
ABSTRACT: Reflection has a long history as an assessment mode in teaching and learning for higher education, and particularly for teacher education. However, past studies have not systematically analysed how attributes of students, content, and feedback are linked to the quality of students' reflections in journal writing. To fill the gap, this exploratory study examines 1, 210 journal entries by 121 university students in a General Education course. We apply multilevel, cross-classification, ordered logit analysis to test the explanatory model. Results show that entries written by young women (vs. young men) written later in the course, with personal content (vs. academic or societal), or following teacher or student feedback had higher teacher ratings for reflection, compared to other entries. These results suggest the importance of gender, time, journal content, and feedback to raising reflection quality.